The Use of Padlet Application in Improving the Ability to Write News Texts of Class VIII Students of SMP Muhammadiyah - Syekh Adiwijaya; Anin Asnidar; Nurhalisa Said (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This research is quantitative that aims to test the cause-and-effect relationship between variables by providing treatment. This method is used to measure the influence of using padlet applications in learning to write news texts. This research uses a Pre- Experimental design. In this study, researchers used Pre-Experimental Design with the One-Group Pretest-Posttest Design type, namely in this study there is a pretest before being treated. Based on the results of research and discussion, it was found that the ability to write student news texts before applying the padlet application is still in the category of inadequate and sufficient. This is because in the text structure indicator, students are still unclear, chaotic in the text structure, the text structure is not organised and there are some unclear parts. This research describes the ability of students to write news after applying the padlet application where on the indicators of text structure, content/idea development, language use, creativity, and the suitability of theme, the student's news writing ability, most students are already in the good and very good categories.